HARMONISASI PENGATURAN PEMANFAATAN ENERGI PANAS BUMI PADA HUTAN KONSERVASI - Zakaria, Aditya Darmawan (Universitas Negeri Surabaya, 2020)
Utilization of Geothermal energy has an important role in a country that has abundant energy reserves like in Indonesia today. Utilization of Geothermal energy serves to create domestic energy independence. The Geothermal Energy Utilization Policy itself has been regulated in Law Number 21 of 2014 concerning Geothermal Energy. However, regarding the location of the utilization of geothermal energy, there is a disharmony with Law No. 41 concerning Forestry, which in Article 38 (1) of Forestry it is emphasized that the use of forest areas for development purposes outside forestry activities can only be done within production forest areas and areas protected forest. Another problem that often arises is social problems around the PLTP field. Often in its management a company violates several rules so that it affects the environment around the region. An example of the problem is the Baturaden PLTP project on the slopes of Mount Selamet. Hundreds of people from various elements of the community held an action demanding the termination of the PLTP project. The purpose of this research is to analyze the form of norm disharmony between Law Number 21 of 2014 concerning Geothermal and Law Number 41 of 1999 concerning Forestry in granting permits for the use of Geothermal Energy in conservation forests. This type of research used in this study is normative legal research. The research approach used is the statutory approach, the concept approach, and the historical / historical approach. Types of legal materials used in this study are primary legal materials and secondary legal materials. The technique of collecting legal material is done by the method of library study which is then processed by the selection of legal materials in data processing techniques. Legal materials are then drawn conclusions and then provide a prescriptive about the results of research. The results of this study indicate that there is disharmony in regulating the utilization of geothermal energy in conservation forests due to the formation of legislation in different periods made by different institutions, differences between various laws or regulations and overlapping authorities and Conflicts of interest between institutions within the government resulting in differences in interpretation in its implementation, harmonization and synchronization of the law with the provisions of other laws relating to both the old and new laws also need to be done, including harmonization related to the substance of the division of government affairs central and regional government in the Law on Regional Government, harmonizing criminal provisions and administrative sanctions in the Law on Prevention and Eradication of Forest Destruction, harmonizing environmental protection and management in the Law on Protection and Environmental Management, alignment of forest management in the Law on Spatial Planning, Dispute resolution can be carried out through litigation and non-litigation. Keywords: Geothermal, Conservation Forest, Energy